Assessing Cost-Effective Materials for Multi-Functional Crutches: an Integrated MCDM Framework - M. Joshi (Archives of Metallurgy and Materials)
Material selection significantly impacts crutch performance and durability, posing challenges due to various criteria and complex decision-making in engineering design. This study introduces an innovative methodology for evaluating material options in developing cost-effective multifunctional crutches. Integrating the CRITIC method for factor weighting, MARCOS for alternative measurement and ranking, and TOPSIS for preference ranking, the framework assesses seven potential materials across ten criteria. Key findings highlight cost, adjustability, and density as critical factors, with aluminium identified as the optimal frame material followed by fiberglass, striking a balance between attributes. Sensitivity analysis confirms the robustness of this approach, providing valuable insights for material selection in engineering systems and assistive technology design, enhancing crutch performance and user satisfaction. This novel approach combines established decision-making techniques, enhancing the efficiency of material selection processes for crutch design.